2011
DOI: 10.1002/app.35096
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity modeling of carbon black/polycarbonate, carbon nanotube/polycarbonate, and exfoliated graphite nanoplatelet/polycarbonate composites

Abstract: Adding conductive carbon fillers to electrically insulating thermoplastic polymers increases the resulting composite's electrical conductivity, which would enable them to be used in electrostatic dissipative and semiconductive applications. In this study, varying amounts of carbon black (CB: 2 to 10 wt %), multiwalled carbon nanotubes (CNT: 0.5 to 8 wt %), or exfoliated graphite nanoplatelets (GNP: 2 to 15 wt %) were added to polycarbonate (PC) and the resulting composites were tested for electrical conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
(47 reference statements)
2
14
0
Order By: Relevance
“…The average values of σ for microparts with lower CNT concentrations (<7 wt%) are not available because they are outside of the measurement scale for the Keithley electrometer, indicating that a higher filler concentration is required to attain sufficient conductive pathways within subsequent microparts. In contrast, Via et al reported that the percolation threshold ( p c ) for CIM PC/CNT macroparts is about 1.7 wt% (1.2 vol%). Moreover, they reported that the σ reached 2.2 × 10 −4 S/cm of PC‐2 macroparts, which is nearly 6 orders of magnitude higher than that obtained in μIM, indicating that the difference in shearing conditions plays a pivotal role in determining the microstructure of subsequent moldings.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The average values of σ for microparts with lower CNT concentrations (<7 wt%) are not available because they are outside of the measurement scale for the Keithley electrometer, indicating that a higher filler concentration is required to attain sufficient conductive pathways within subsequent microparts. In contrast, Via et al reported that the percolation threshold ( p c ) for CIM PC/CNT macroparts is about 1.7 wt% (1.2 vol%). Moreover, they reported that the σ reached 2.2 × 10 −4 S/cm of PC‐2 macroparts, which is nearly 6 orders of magnitude higher than that obtained in μIM, indicating that the difference in shearing conditions plays a pivotal role in determining the microstructure of subsequent moldings.…”
Section: Resultsmentioning
confidence: 91%
“…In contrast, Via et al reported that the percolation threshold ( p c ) for CIM PC/CNT macroparts is about 1.7 wt% (1.2 vol%). Moreover, they reported that the σ reached 2.2 × 10 −4 S/cm of PC‐2 macroparts, which is nearly 6 orders of magnitude higher than that obtained in μIM, indicating that the difference in shearing conditions plays a pivotal role in determining the microstructure of subsequent moldings.…”
Section: Resultsmentioning
confidence: 91%
“…Similar ER values have been reported in the open literature for GNP composites in other thermoplastics. For example, XG Sciences's xGnP graphene nanoplatelets (5 μm average particle diameter with a thickness of 6–8 nm) in polycarbonate that were also extruded and injection molded had a percolation threshold of 7.4 wt% (4.6 vol%) .…”
Section: Resultsmentioning
confidence: 99%
“…At least five samples were tested for each formulation. Additional detailed test method information is shown elsewhere .…”
Section: Methodsmentioning
confidence: 99%
“…Carbon nanotubes and other carbon fillers have also been used to increase polymer conductivity, and could potentially be used in the conductive layers (Sandler et al, 1999, Kim et al, 2010, Via et al, 2012. However, our eutectic blends have higher conductivity than composites of conductive polymers or carbon reported in the literature.…”
Section: C Onclusions and Future Workmentioning
confidence: 84%